2007
DOI: 10.1002/adma.200602250
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Functional Mesolamellar Nanocomposites Based on Inorganic/Polymer Intercalation in Purple Membrane (Bacteriorhodopsin) Films

Abstract: Fabrication of self-assembled structures using multiple building blocks with diverse functionalities such as biomolecules, polymers and inorganic nanoparticles has attracted considerable interest due to the potential applications of hybrid constructs in biotechnology and bio-electronic devices. [1,2] A principal candidate biomolecule for incorporation into multi-functional devices is the photoactive protein-retinal complex, bacteriorhodopsin (BR), [3] which acts as a light-activated proton pump in the purple m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Clay minerals of layered organic-inorganic hybrid materials resembling the talc parent structure Si 8 Mg 6 O 20 (OH) 4 have been synthesized by a sol-gel reaction in ambient conditions, with various combinations of metal ions such as magnesium, nickel, and zinc. [2][3][4][5] Their organofunctionalities have also been extensively investigated to improve biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clay minerals of layered organic-inorganic hybrid materials resembling the talc parent structure Si 8 Mg 6 O 20 (OH) 4 have been synthesized by a sol-gel reaction in ambient conditions, with various combinations of metal ions such as magnesium, nickel, and zinc. [2][3][4][5] Their organofunctionalities have also been extensively investigated to improve biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The cationic and water-soluble properties of AMP clay have been used to construct hybrid materials with biomolecules and drug delivery systems. [8][9][10][11][12][13] Considering AMP clay is a nontoxic host material, 14 it should have high potential as a promising drug delivery carrier. There have been a few reports indicating the application of AMP clay as an efficient drug delivery system; 9,11-13 however, most of the previous studies were limited to in vitro evaluation.…”
mentioning
confidence: 99%
“…It has been shown that hybrid lms consisting of PM sheets intercalated with a condensed organosilane can be formed by adding an aqueous precursor to a PM lamellar lm and then allowing the samples to dry. 12,16,17 These composite lms demonstrate enhanced mechanical tolerance and solvent resistance in addition to functional photocycle and photochromic responses. Importantly, the composite lms retain their lamellar structure as opposed to dispersal of the PM sheets randomly within an organic or inorganic supporting matrix.…”
mentioning
confidence: 99%
“…Intercalation in PM lms of non-sol-gel precursors such as polysaccharides, inorganic polymers and polycationic organoclay oligomers has also been demonstrated, but the mechanism by which the guest materials permeated into the PM host structure was not fully elucidated. 16,18 In this paper we have used X-ray surface scattering to study the mechanism of formation of PM lms intercalated with aminopropyl silicic acid (APS) or cationic oligomers of aminopropyl-functionalised magnesium phyllosilicate (AMP), as two model guest species presented in molecular or molecularcluster forms, respectively. Both of these guests have been previously used to produce PM-based composite lms with an AB-type lamellar structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation